Ostrich (Struthio camellus) carcass yield and meat quality parameters - Balog, Augusto [UNESP] (2007)
This article aimed at compiling recent studies on the main factors that influence ostrich meat quality and carcass yield. Few articles investigated the effect of subspecies, which generally are not even mentioned. There are important dietary effects, particularly those caused by dietary protein to energy ratio. Rigor mortis follow-up studies showed that there are no losses in meat quality when carcasses are hot-deboned. Age at slaughter influences some meat quality traits, such as tenderness and lipid content. Few effects of gender have been observed, and at the same age at slaughter, both male and female present the same meat quality traits.